Climate change and temperature rise: implications on food poisoning cases in Malaysia - Hassan, Noor Artika; Hashim, Jamal Hisham; Wan Mahiyuddin, Wan Rozita; Faisal, Mohd Syazwan; Mohd Fuzi, Mohd Fadzli (2018)
Background/Aim: This study is an attempt to quantify climate-induced increases in morbidity rates of food poisoning cases. Methods: Monthly food poisoning cases and average monthly meteorological data from 2004 to 2014 were obtained from the Malaysian Ministry of Health and Malaysian Meteorological Department, respectively. Population projections in Malaysia, up to the year 2040 were adopted from the Malaysian Department of Statistics and modified to the year 2100. The PRECIS model was used to project future climate up to the year 2100 under the A1B scenario. Poisson generalized linear models were developed to quantify the relationship between climatic parameters and the number of reported food poisoning cases in the future. Results: The findings revealed that the total number of food poisoning cases in Malaysia during the 11 years study period was 134,820 cases with 46 deaths. The mean age of the patients was 20±18 years. Half of the cases were among the ages of 13-24 years old. Among the cases, 98.2% were Malaysians and 55.7% were females. The PRECIS model projection under the A1B scenario showed that the surface temperature in Malaysia has a monotonic increment for all states with slightly higher warming rates over the Southern and Northern regions, with an increase of more than 3.0 °C towards the end of the 21st century. Temperature gave a significant impact on the incidence of food poisoning cases in Selangor (p<0.001), Melaka (p<0.001), and Kelantan (p<0.001). For a 1.0°C increase in temperature, the excess risk of food poisoning in each state will increase up to 56.4%. Conclusion: The study concludes that climate does affect the distribution of food poisoning cases in Selangor, Melaka, and Kelantan. Food poisoning cases in other states are not directly associated with temperature but related to long term trends and seasonality.